Exploring the Factors Influencing Mothers Brand Choices on Baby Diaper Brands (An Applied Marketing Research) - Pavithra, S.; Niththiya, N.; Shivany, S. (International Conference on Contemporary Management (ICCM-2016), Conducted by Faculty of Management Studies and Commerce, University of Jaffna, 2016)
The Jaffna market is idiosyncratic, and furnishes opportunities for marketers to sell their products and services to potential customers who have returned to their habitual life. Knowing mothers' brand choices is essential for creating strategies for baby items in the market. Using the Grounded Theory approach, this study explores how marketing academics and marketers can gain fresh insights into mothers' behaviour of baby diaper products in the post-conflict marketing environment. By using this methodology, the researcher analyzed 40 in-depth interviews with mothers in the post-conflict marketing environment. This approach allowed the development of new knowledge about the mothers' purchase behaviour on diaper brands. The researcher identified unique behavioural patterns in the consumer brand choice, in a post-conflict marketing environment. The findings of the study show that mothers are seeking better benefits, such as hygiene, absorbency, comfort, user-friendly, green ingredients, environmental friendliness, price, softness and stretch, fashion and style, safety and secure, size and weight, which are a match with their living patterns cultural norms, as well as the baby's care. Especially they are more concern about brand benefits, which match the needs of the society. This research has an implication to design a unique strategy to attract the mothers to purchase particular brand in the country.
Keywords: Baby diaper brands, Grounded theory approach, Mothers' brand choice post-conflict marketing environment.